2022
DOI: 10.1038/s41550-022-01754-4
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of a magnetohydrodynamic disk wind traced by water maser observations

Abstract: The formation of astrophysical objects of different nature and size, from black holes to gaseous giant planets, involves a disk-jet system, where the disk drives the mass accretion onto a central compact object and the jet is a fast collimated ejection along the disk rotation axis. Magnetohydrodynamic disk winds can provide the link between mass accretion and ejection, which is essential to ensure that the excess angular momentum is removed from the system and accretion onto the central object can proceed. How… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 40 publications
4
46
0
Order By: Relevance
“…The most direct observational evidence of the magnetocentrifugal mechanism and the acceleration of the jet as described here is provided by the recent observations of the most massive young stellar object (M = 5.6 ± 2.0M ) in the starforming region IRAS 21078+5211 (Moscadelli et al 2022(Moscadelli et al , 2021. In Moscadelli et al (2022), 22 GHz water maser observations (which trace internal shocks of the gas), were able to uncover the helical trajectories of the plasma as it is magnetocentrifugally ejected.…”
Section: Acceleration Of Materials In the Jetmentioning
confidence: 74%
See 4 more Smart Citations
“…The most direct observational evidence of the magnetocentrifugal mechanism and the acceleration of the jet as described here is provided by the recent observations of the most massive young stellar object (M = 5.6 ± 2.0M ) in the starforming region IRAS 21078+5211 (Moscadelli et al 2022(Moscadelli et al , 2021. In Moscadelli et al (2022), 22 GHz water maser observations (which trace internal shocks of the gas), were able to uncover the helical trajectories of the plasma as it is magnetocentrifugally ejected.…”
Section: Acceleration Of Materials In the Jetmentioning
confidence: 74%
“…The most direct observational evidence of the magnetocentrifugal mechanism and the acceleration of the jet as described here is provided by the recent observations of the most massive young stellar object (M = 5.6 ± 2.0M ) in the starforming region IRAS 21078+5211 (Moscadelli et al 2022(Moscadelli et al , 2021. In Moscadelli et al (2022), 22 GHz water maser observations (which trace internal shocks of the gas), were able to uncover the helical trajectories of the plasma as it is magnetocentrifugally ejected. In that article, we used the simulation corresponding to the fiducial case with grid x16 to produce a snapshot comparison when the protostellar mass is similar to the observed value, and found that the geometry and kinematics of the transition region where the flow abandons the Alfvén surface and becomes helical coincide very well with the observed masers.…”
Section: Acceleration Of Materials In the Jetmentioning
confidence: 74%
See 3 more Smart Citations